The Effect Of Using Video Learning Media On Critical Thinking Skills On The Topisc Of Environmental Pollution - Jannah, Rodatul; Pramudiyanti, Pramudiyanti; Meriza, Nadia (Universitas Lampung, 2023)
This study aims to determine the effect of instructional video media on critical thinking skills. The population of this study were all seventh grade students at SMPN 25 Bandar Lampung. The research design used in this study is a quasi-experimental design in the form of a non-equivalent control group design. The sample in this study were students from 2 classes, namely class VII C and VII D, which were selected using cluster random sampling technique. The research instrument used a pretest-posttest research sheet. Data on the average value of pretest-posttest, n-gain as a result of increasing students' critical thinking skills were analyzed by statistical tests, namely the Mann Whitney test. The results showed that students' critical thinking skills were in the